An analysis of the five-wire distribution system. - Ward, D.J (IEEE Transactions on power delivery)
Most power distribution systems in North America employ a four-wire multi-grounded neutral design. A five-wire distribution design has been proposed and studied in a project cosponsored by EPRI, the Empire State Electric Energy Research Corporation, the New York State Electric and Gas Corporation, and the New York State Energy Research and Development Authority. While summary information on the project claims five-wire distribution is a viable means of dealing with stray voltage, magnetic fields and high impedance faults, it does not appear that a balanced assessment has been presented. The purpose of this paper is to summarize the significant differences between the five-wire distribution system and the conventional four-wire multigrounded neutral system. Both four-wire and five-wire distribution are assumed to be multigrounded systems.